Prospects and Challenges of Malaysia's Distributed Energy Resources in Business Models Towards Zero – Carbon Emission and Energy Security - Nur Iqtiyani Ilham; Mohamad Zhafran Hussin; Nofri Yenita Dahlan; Eko Adhi Setiawan (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
For a decade, distributed energy resources in Malaysia have growth as one of the paths in battling with sustainable energy crisis and environmental pollution. Several intriguing initiatives and incentives have been established to encourage the use and sales-side of renewable energy at the distribution consumers. However, Malaysia's distributed energy resources penetration is still at its slow pace, with only 7.6% (excluding large hydropower) shared in energy mix generation. Therefore, innovation in power systems is required to drive the uptake of distributed energy resources. This paper reviews the business model innovation that allows distributed energy resources to participate in national grid services and the wholesale electricity market. Different technical and non-technical challenges with high shares of variable renewable energy in power systems are highlighted, and the current update on compensation scheme, Net-Energy-Metering 3.0 is also discussed. Along with these challenges, stance the prospect of adopting distributed energy resources innovation projects such as peer-to-peer energy trading and virtual power plant in the electricity market. It could further furnish the benefits to a better environmental and power system in terms of carbon dioxide avoidance, grid flexibility and increase revenue for distributed energy resources owners respectively. Through the review, it led to observation that policy and regulatory in Malaysia are the main factors in accelerating the distributed energy resources deployment. Therefore, the abilities and roles of Malaysia Energy Commission and Sustainable Energy Development Authority as a regulator and implementing agencies are crucial in determining the present and future distributed energy resources business model.